Sieving Test for Malt – Determination of Accuracy, Repeatability and Reproducibility: Submitted on behalf of the Analysis Committee of the European Brewery Convention - Schmitt, M.; Home, S. (BrewingScience, 2006)
EBC method 3.11.1, Sieving Test for Barley, was modified and tested for malt. Six samples were analysed in 12 laboratories. Fractions I – IV and the amount of broken kernels and foreign matter were analysed in duplicate. Repeatability and reproducibility figures were determined for the combined fraction I + II, fraction IV, broken kernels and foreign matter. Repeatability (r95) of fractions, except broken kernels, were independent of the mean value. Reproducibility (R95) of fraction IV was independent of the mean and other fractions were dependent on the mean value. All results were acceptable and the method was recommended for inclusion in Analytica-EBC.